Social behavioral change communication - an approach to vaccine hesitancy - S., Suthanthira Kannan; Rajeshwari, Swetha; Ramasamy, Aarthy (International Journal Of Community Medicine And Public Health, 2021)
While the proportion of a population needed to be vaccinated against COVID-19 to achieve herd immunity has not yet been established, addressing COVID-19-related vaccine hesitancy is expected to lead to greater numbers of vaccinated individuals, in turn resulting in fewer COVID-19 cases, reduced infection transmission and fewer deaths. Reasons for vaccine hesitancy are influenced by a spectrum of factors from individual belief system to external sources of information. We need to adopt a multi-pronged approach which involves socio demographic domains to achieve herd immunity.